Tourist attractiveness of selected small towns in Lower Silesia - Zakrzewska-Półtorak, Alicja; Chwastyk, Dominika; Pluta, Agata (Atrakcyjność turystyczna wybranych małych miast województwa dolnośląskiego, 2018)
The aim of the article is to present the results of the research involving identifying tourist attractiveness of selected small towns in Lower Silesia as well as comparing its level to the level of tourist function’s development in these towns. The study covered 10 out of 72 small towns in Lower Silesia. The study was based on data from 2014 to 2017. The authors use a two-dimensional indicator of the tourist function, they construct a synthetic indicator of tourist attractiveness, and then they compare obtained results for the analyzed small towns. The study demonstrates that tourist attractiveness of a small town depends on tourist values which were studied, but not just. According to the authors, the level of tourist flows is influenced additionally by: the attractiveness of the environment, tourists’ habits, information and marketing activities of specific towns and enterprises offering tourist-recreation accommodation and other tourist attractions, the state of the transport infrastructure and the quality of public transport links. The research procedure was conducted with use of descriptive methods, quantitative methods and graphics methods
Biblioteka Regionalisty, 2018, Nr 18, s. 79-92
Keywords: town; city; development of tourist; facilities; tourist accommodation; tourist values; miasto; zagospodarowanie; baza turystyczna; walory turystyczne